Uma sequência didática com o ensino híbrido no estudo de conteúdos da cinemática - Simões, Marco Aurélio Ferreira (2019)
In this work we propose the planning and implementation of a didactic sequence with the blended learning in the study of kinematics content, specifically the contents referring to the concepts of relative velocity, encounter and overruns of uniform and uniformly varied rectilinear motions, considering first-year students of a public high school in the city of Manaus. The idea is to engage students in the development of an artifact whose theme involves these concepts. In this case, students should employ the learning of content about movements to respond to the demands of the project. They should research the internet, on scales and model Assembly, in order to apply it in the execution stage of the project. Make use of a miniature cars to demonstrate uniform rectilinear motion. Students should develop a presentation in the form of a video to expose the creation process and the concepts that can be visualized, from the concept of frame of reference, to those of relative velocity and encounters and overruns.